Fundamental of Entrepreneurship ENT300: Uni-Sport Center / Muhammad Nazirin Khairuddin ... [et al.] - Khairuddin, Muhammad Nazirin; Harun, Muhammad Amin; Johari, Mohadzrin; Kamaruddin, Mohammad Nazrul; Morhaili, Mohamad Taufik (2011)
In Kota Samarahan, have one company that also servicing futsal and badminton. So that we take want to take this opportunity to get involved in this type of business. Thus, there is only one competitor in Kota Samarahan which is Golden Hawk Company. Even though this business maybe have a competitor, we believe that we can success to fight against our competitor because we have a advantage that we providing a world class futsal and badminton service- In the future we believe that we can be the best company that providing futsal and badminton services in Kota Samarahan and perhaps whole Sarawak because we have a good management for customer, quality of service, worker, strategic place and pus provide a world standard sport. Besides, we also provide "take five cafe" a simple cafe which can refreshing our customer with isotonic drink. Our business is fully targeting people between 15-40 years old and especially for university students from Unimas, iptar and uitm. we have a strategies to attract customers which is by giving a discount by time to time. Business plan is all about the information gathered regarding the projects to predict viability, forecast success and propose strategies for the company-Administrative planning is divided by two periods.